Trophic ecology of the fish Arothron meleagris (Tetraodontiformes: Tetraodontidae) from Los Frailes reef, Southern Baja California, Mexico - Moreno, Xchel G. (2009)
Monthly samples were taken from November 2004 to October 2005 in the Los Frailes reef, BCS, Mexico. The objective was to determine the feeding habits of the pufferfish, Arothron meleagris, as well as possible variations in feeding patterns due to size and/or sex. We captured 101 specimens, with all stomachs contained food. The index of relative importance (IRI) was used to determine the main items; which were non-identified organic matter (NIOM) (30.44%), Echinometra vanbrunti (26.25 %), Porifera (12.63 %), Pocillopora spp. (11.84%), Bryozoa (5.37 %) and Porites spp. (4.83 %). Levin’s index indicated a low trophic niche breadth (Bi= 0.12) and allowed us to determine that A. meleagris is a specialist predator with strong preferences towards certain food types. The Morisita-Horn index showed a high trophic overlap between sexes (Cλ=0.78), seasons (hot and cold Cλ=0.95) and among sizes (small and medium Cλ=0.94; small and large Cλ=0.74; medium and large Cλ=0.83)